The effect of the Coca-Cola transfer pricing cases and selected shifts in the international tax regime on the determination of an arm's length price - Gutsche, Janet (Department of Commercial Law, 2023)
An era of legal loopholes and opportunities for double non-tax, along with economic, social and political developments in modern history have driven significant changes in the international tax environment facing taxpayers with cross border interests. Transfer pricing and the arm's length calculation is central to this issue. The proposition is that corporate tax evasion scandals and demanding government budget deficits have led to global shifts in the international tax environment. This has redefined the future of tax planning and may pose a threat to the rights of ethical and responsible international taxpayers intending to pay, only, their fair share of taxes. The Coca-Cola Company is one of the most prominent and best known international organisations. Its vast and intricate international business structure and transfer pricing challenges are universal, relatively easy to understand, and relatable to other corporate taxpayers. The company has a significant presence in South Africa and 2 out of the 8 subsidiaries that were involved in the transfer pricing cases are African (Lesotho and Egypt).1 These cases that have been proceeding since before 2017 are useful examples for anyone attempting to understand how the arm's length principle will be applied in the modern international tax era. There is insufficient transfer pricing case law, specifically in South Africa, where the prevailing transfer pricing guidelines are contained in a practice note2 that has remained unchanged since its introduction in 1999.3 The lack of precedent makes decisions regarding an appropriate arm's length price uncertain. It is necessary to analyse pertinent foreign case law that may provide guidance on how tax authorities and practitioners in South Africa may apply transfer pricing regulations. The aim is to adopt the case study method to analyse the Coca-Cola transfer pricing cases in light of selected shifts in the international tax regime to explore what effect will be had on the determination of an arm's length price going forward.